Eating behavior trajectories in the first ten years of life and their relationship with BMI - Herle, Moritz (Int J Obes (Lond), 2020)
BACKGROUND: Child eating behaviors are highly heterogeneous and their longitudinal impact on childhood weight is unclear. The objective of this study was to characterize eating behaviors during the first ten years of life and evaluate associations with BMI at age 11 years. METHOD: Data were parental reports of eating behaviors from 15 months to age 10 years (n=12,048) and standardized body mass index (zBMI) at age 11 years (n=4884) from the Avon Longitudinal Study of Parents and Children. Latent class growth analysis was used to derive latent classes of over-, under-, and fussy eating. Linear regression models for zBMI at 11 years on each set of classes were fitted to assess associations with eating behavior trajectories. RESULTS: We identified four classes of overeating; “low stable” (70%), “low transient” (15%), “late increasing” (11%), and “early increasing” (6%). The “early increasing” class was associated with higher zBMI (boys: β=0.83, 95%CI:0.65, 1.02; girls: β=1.1; 0.92, 1.28) compared to “low stable”. Six classes were found for undereating; “low stable” (25%), “low transient” (37%), “low decreasing” (21%), “high transient” (11%), “high decreasing” (4%), and “high stable” (2%). The latter was associated with lower zBMI (boys: β=-0.79; -1.15, -0.42; girls: β=-0.76; -1.06, -0.45). Six classes were found for fussy eating; “low stable” (23%), “low transient” (15%), “low increasing” (28%), “high decreasing” (14%), “low increasing” (13%), “high stable” (8%). The “high stable”class was associated with lower zBMI(boys: β =-0.49; -0.68 -0.30; girls: β =-0.35;-0.52, -0.18). CONCLUSIONS: Early increasing overeating during childhoodis associated with higher zBMI at age 11. High persistent levels of undereating and fussy eating are associated with lower zBMI. Longitudinal trajectories of eating behaviors may help identify children potentially at risk of adverse weight outcomes.